INSURANCE LITERACY AND RISK APPETITE: EVIDENCE FROM SELECTED SMALL AND MEDIUM-SIZED ENTERPRISES IN LAGOS, NIGERIA: Array - Ajemunigbohun, Sunday Stephen; BANJO, Kudirat Adeola; SAKA, Toyin Shafau (Acta Universitatis Danubius. Œconomica, 2022)
The economic loss that possibly occurred from the inactions of individuals may be resultant effects due to lack of insurance literacy in their personal financing decisions. However, insurance decisions that rest upon the level of risk acceptability of an individual SMEs is usually expressed in the course of attaining a high level of personal financial satisfaction. Therefore, this study examined the relationships between insurance literacy, and risk appetites, with specific reference to SME operators/owners in Lagos, Nigeria. The study adopted a cross-sectional survey research design. Thus, the single-stage cluster sampling method was adopted in the questionnaire distribution and collection processes. A structured questionnaire was employed for data gathering. A total of 386 copies of the questionnaire were distributed, of which 273 were found usable which represented a 71% response rate. The data procedural technique employed were simple frequency percentages and the multivariate regression method. The results show that all other determinants of insurance literacy except for insurance behaviour have positive relationships with SMEs’ risk appetites in Lagos, Nigeria. This study recommended that insurance education, as a field of study, should be taken as seriously as possible so that it can help develop the peoples’ minds psychologically and sociologically to get attracted to insurance in order to manage their future. More so, insurance providers in Nigeria should attempt to make the business of insurance lovable and affordable to SMEs’ operators/owners in a bid to shapen their behavioural risk attitudes.